(untitled) (Journal of Nobel Medical College, 2018)
Background : Breast cancer is one of the commonest cancers in female. FNAC is safe and cost affective screening test for breast lump having both high sensitivity and specificity. Our aim is evaluation of diagnostic accuracy of fine needle aspiration cytology [FNAC] in diagnosis of breast lesions. Material and Methods: All male and female patients with breast lesion were subjected to cytological evaluation of which many were followed up with histopathological evaluation to assess the diagnostic accuracy of FNAC. Results : Out of 1088 cases diagnosed on FNAC, 703 cases (64.61%) were benign and 232 cases (21.3%) were found to be malignant. In our study the most common benign lesion was fibroadenoma and commonest malignant lesion was Duct carcinoma. Maximum cases of breast lesions in females were in the age group of 21- 30 years followed by age group of 31- 40 years. While maximum cases in males were in the age group of 31-40 years & 61-70 years. The sensitivity and specificity of FNAC for cyto-histo correlation were found to be 97.16% and 92.83% respectively. Conclusion : FNAC is a highly sensitive and specific test for diagnosis and categorization of breast lesions into different categories of neoplastic and non-neoplastic breast lesions. Journal of Nobel Medical College Volume 6, Number 2, Issue 11, July-December 2017, 66-71